Impacts of Lorentz invariance violation on particle acceleration and emission - Francisco, Matheus Duarte (2025)
Einsteins theory of relativity, along with Lorentz invariance, forms a cornerstone of modern physics. A potential violation of Lorentz symmetry could point the way towards a quantum gravity model. However, the effects of such a violation are expected to be minimal, becoming significant only at extreme energy scales. This work aims to utilize ultrahigh- energy cosmic rays to study the limits of this symmetry, specifically addressing the gap in understanding the effects of Lorentz Invariance Violation on acceleration processes. In this study, first and second-order Fermi mechanisms were analyzed, and to incorporate Lorentz invariance violation, a modified dispersion relation and an altered Lorentz factor were used. The second-order mechanism exhibited a shift in the spectral index and a reduction in acceleration time. On the other hand, the first-order mechanism showed significant suppression in the particle energy spectrum, prompting a comparison with the spectrum observed by the Pierre Auger Observatory. Furthermore, synchrotron and inverse Compton energy loss processes were investigated from the perspective of symmetry breaking. Using first-order acceleration as a baseline and applying the one-zone model, the effects on both the charged particle spectrum and photon emission spectrum were explored. For synchrotron radiation, an energy barrier was obtained, along with a notable suppression in the charged particle and photon spectra. The inverse Compton model revealed significant suppression in the particle spectrum and the emergence of a new high-energy photon emission region beyond current expectations. This new emission region was compared with data from Markarian 501, and an illustrative contrast of the integrated spectrum in this region was made with the photon flux limits set by the Pierre Auger Observatory.